2013
DOI: 10.1007/s11605-012-2012-5
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes of Laparoscopy Combined with Enhanced Recovery Pathway after Ileocecal Resection for Crohn’s Disease: a Case-Matched Analysis

Abstract: This is the first reported experience of laparoscopy with ERP in CD patients and suggests that optimized perioperative care combined with minimally invasive techniques may lead to further improvements in surgical outcomes for CD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…Conversion to laparoscopy was easy to perform owing to the configuration of the robotic arms that allowed the assistant and the surgeon to access the patient rapidly. The postoperative major complication (Clavien–Dindo ≥3) rate was 4.4%, which does not differ significantly from the overall results after minimally invasive surgery previously reported from our practice . The haptic feedback, alerting the surgeon of possible inadvertent damage while moving the instruments, could have played a role in preventing intra‐operative complications.…”
Section: Discussionsupporting
confidence: 44%
“…Conversion to laparoscopy was easy to perform owing to the configuration of the robotic arms that allowed the assistant and the surgeon to access the patient rapidly. The postoperative major complication (Clavien–Dindo ≥3) rate was 4.4%, which does not differ significantly from the overall results after minimally invasive surgery previously reported from our practice . The haptic feedback, alerting the surgeon of possible inadvertent damage while moving the instruments, could have played a role in preventing intra‐operative complications.…”
Section: Discussionsupporting
confidence: 44%
“…In favor of avoiding bowel preparation and implementing minimally invasive surgery whenever possible, an enhanced recovery pathway without MBP in laparoscopic CD surgery did not lead to increased complication rates with shorter hospital stay in a study by Spinelli et al. [28]. Notably, SSI per se were not reported in the study but Clavien-Dindo grade I–II complications (which included opening of a wound at the bedside) were similar.…”
Section: Discussionmentioning
confidence: 90%
“…Nutritional guidelines merge with enhanced recovery after surgery (ERAS) guidelines [65], which are beneficial for surgical patients regarding outcome, length of stay, and costs. Recent reports suggested that enhanced recovery combined with minimally invasive techniques may lead to further improvements in surgical outcomes of Crohn’s patients [66,67]. Whenever possible, elective surgical patients should be treated according to the ERAS protocol: avoidance of long term fasting, integration of nutritional strategies into the overall management of the patient, metabolic homeostasis, and early mobilization [4].…”
Section: Discussionmentioning
confidence: 99%